2020
DOI: 10.4103/jfmpc.jfmpc_870_20
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of knowledge, attitudes, and practices toward COVID-19 virus among university students in Kurdistan region, Iraq: Online cross-sectional study

Abstract: Background and Aim: The World Health Organization (WHO) declared the novel coronavirus infection COVID-19 as a pandemic on March 11, 2020. Adherence to infection control measures is potentially influenced by people's knowledge, attitudes, and practices (KAP) about the infection. This project was performed to assess the KAP toward COVID-19 of university students in Kurdistan Region, Iraq. Materials and Methods: An online cross-sectional study was performed in April 2020 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…This variation in the knowledge is related to other countries' sociodemographic and is probably reflected in the knowledge about typical COVID-9 symptoms. In the current study, 84.7% of the participants had good knowledge about typical symptoms of COVID-19, like other studies [2,7,14,20,22,23]. On the other hand, other studies showed <80% had poor knowledge about typical symptoms of COVID-19 [16,17].…”
Section: Discussionsupporting
confidence: 71%
“…This variation in the knowledge is related to other countries' sociodemographic and is probably reflected in the knowledge about typical COVID-9 symptoms. In the current study, 84.7% of the participants had good knowledge about typical symptoms of COVID-19, like other studies [2,7,14,20,22,23]. On the other hand, other studies showed <80% had poor knowledge about typical symptoms of COVID-19 [16,17].…”
Section: Discussionsupporting
confidence: 71%
“…The role of individual, broader societal factors (social norms) and political (trust in Government) factors in vaccine hesitancy in Iraq reinforces the need for clear public health messaging which addresses citizen's concerns in relation to these factors. Public knowledge about COVID-19 is generally considered to be high in Iraq [30,31]. However, like many other nations, Iraq has seen increases in the use of social media to share inaccurate information about COVID-19 [32].…”
Section: Vaccine Hesitancymentioning
confidence: 99%
“…This study aimed to evaluate medical students' state during the COVID-19 pandemic and assess their knowledge, attitudes, and practices toward E-learning, the leading way to deliver knowledge during the pandemic outbreak in the Kurdistan Region of Iraq. Another study in the region demonstrated medical students' knowledge, attitudes, and practices towards the COVID-19 virus [15]. In this study, students from seven regional medical schools were recruited, and the sample included 500 medical students from all stages.…”
Section: Discussionmentioning
confidence: 99%